2002
DOI: 10.1210/jcem.87.7.8573
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Consequences of Early-Onset Growth Hormone Excess

Abstract: Acromegaly has relevant effects on the cardiovascular system, but few data deal with the early effects of GH and IGF-I excess. To study the early stage of acromegalic cardiomyopathy and give indirect evidence of the mechanisms underlying GH and IGF-I action on the human heart, 25 patients with uncomplicated acromegaly [15 young subjects with short-term (< or =5 yr) disease and 10 with long-term (>5 yr) disease] and 25 sex- and age-matched controls were studied. Cardiovascular risk parameters were studied by st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 46 publications
(39 reference statements)
4
16
0
3
Order By: Relevance
“…This disorder can be asymptomatic for years before clinical and instrumental signs of cardiac involvement are noted. In a cohort of 25 patients aged less than 40 years and divided on the basis of presumed disease duration below or above 5 years, we documented an increase in heart rate at rest (84.9^1.2 vs 77.8^1.2 b.p.m., P , 0.001) when compared with gender-and age-matched controls (34). In addition, as expected, the patients had an increase in LVM and a decrease in LV performance that was more evident in the patients with longer disease duration (Fig.…”
Section: Cardiac Involvement In Acromegalysupporting
confidence: 73%
“…This disorder can be asymptomatic for years before clinical and instrumental signs of cardiac involvement are noted. In a cohort of 25 patients aged less than 40 years and divided on the basis of presumed disease duration below or above 5 years, we documented an increase in heart rate at rest (84.9^1.2 vs 77.8^1.2 b.p.m., P , 0.001) when compared with gender-and age-matched controls (34). In addition, as expected, the patients had an increase in LVM and a decrease in LV performance that was more evident in the patients with longer disease duration (Fig.…”
Section: Cardiac Involvement In Acromegalysupporting
confidence: 73%
“…Colao et al conducted a cohort study and classified 25 acromegaly patients aged less than 40 years into 2 groups depending on the disease duration, i.e., less than or more than 5 years. They showed that the patients had an increase in LV mass and a decrease in LV performance, which was more evident in the patients with a longer disease duration (10). On the basis of these reports, we speculate that the present case, showing no clinical symptoms but only changes in the appearance for over 10 years, might have developed acromegaly at least 10 years previously, and cardiovascular complications would have developed gradually during that time.…”
Section: Discussionsupporting
confidence: 54%
“…Dentre as anormalidades morfológicas e funcionais da cardiomiopatia acromegálica, a HVE é a mais característica e também a mais estudada ao longo do tempo (12,19,21,23), porém disfunção sistólica e diastólica também têm sido descritas (23,24,31). A coexistência de outras anormalidades cardiovasculares e metabólicas como hipertensão arterial, intolerância à glicose/diabetes mellitus podem influenciar negativamente no desempenho cardíaco (12).…”
Section: Discussionunclassified
“…Colao e cols. (31), avaliando pacientes acromegálicos submetidos à realização de ecocardiograma e angiografia miocárdica com radionuclídeo, observaram maior fração de ejeção em repouso, mas não no pico do exercício, quando comparados aos controles. Fazio e cols.…”
unclassified